A new species of Cephalaeschna Selys, 1883 (Odonata: Anisoptera: Aeshnidae) from Neora Valley National Park, West Bengal, India, with notes on C. acanthifrons Joshi & Kunte, 2017 and C. viridifrons (Fraser, 1922) - Dawn, Prosenjit (Zootaxa, 2021)
A new species Cephalaeschna patrai sp. nov. is described from Neora Valley National Park, Darjeeling Himalays as the eighth species of the genus from India. This new species is characterized by bright green markings on overall black body color, black is replaced with brown in female. Anterolateral thoracic stripe separated in two patches connected with a narrow line. The cerci are uniformly broad towards end, without any constriction in the lateral view; tip of the same prominently curved upwards to form blunt tubercle which appears to be projected inwards in the dorsal view. An updated key for all the Indian species is provided here. A short note about the affinities among congenerics distributed across Himalayas (particularly C. acanthifrons Joshi & Kunte, 2017 and C. viridifrons (Fraser, 1922)) is also included.